Scholar's strong research benefits industry - New Straits Times, (2011)
SERDANG : UPM Vice-Chancellor, Datuk Ir. Dr. Radin Umar Radin Sohadi believes the university's expertise in teaching, leraning, research and innovation should be put to good use for the betterment of society and to raise the standard of living of the people.